Koncentrace kortizolu ve slinách v průběhu zátěžových situací u úzkostných a neúzkostných adolescentů - Kateřina Kubíková; Isabella Pavelková; Aneta Boháčová (Karolinum Press, 2021)
Objectives. We investigated the biological response of organism to stress in real situations at school in adolescents. We were interested in how stress is manifested in adolescents without anxiety and in adolescents with a tendency to anxiety experiencing. The aim of the study is to analyse changes in salivary cortisol levels during stressful situation at school. Hypotheses. The analyses verified how cortisol levels change in situations associated with the threat of social assessment in the school environment in individuals without anxiety and anxious; H1a-c: Anxiety individuals will have higher cortisol levels in all monitored situations compared to adolescentswithout anxiety. We also focused on the possible links between an individual's tendency to experience anxiety and the type of stress response; H2: Anxiety individuals will show a different development of cortisol levels between situations A, B and C compared to adolescents without anxiety. We also examined the relationships between cortisol levels and cognitive and emotional fear. H3: Anxiety individuals will show significant links between cortisol levels and cognitive and emotional fear in the achievement situation. Methods. The research group was comprised of 238 adolescents in the first phase of the study. The final sample for salivary cortisol analysis was comprised of 38 participants aged 12−14 years. The questionnaires battery contains Piers-Harris II, B-JEPI and TAI. Results. The results show that in both groups of adolescents without anxiety and anxious adolescents, cortisol has a demonstrably different development trend during the day. Furthermore, anxious adolescents showed demonstrably lower cortisol levels at school compared to adolescents without anxiety, in adolescents without anxiety, we observed higher cortisol levels and fall of cortisol level during the day. Our analyses showed that stronger relationships between cortisol and test anxiety are shown especially by anxiety adolescents compared to adolescents without anxiety. Limitations. The limitation is a smaller research sample and the selection of situations in which the level of salivary cortisol was evaluated. The important limitation is the fact that the first sampling was taken at different times after awakening, because the cortisol levels change more dynamically in this part of the day.